GJB2 and GJB6 genes: Molecular study and identification of novel GJB2 mutations in the hearing-impaired argentinean population - Dalamon, Viviana Karina (2010)
Mutations in the GJB2 gene are responsible for more than half of all cases of recessive non-syndromic deafness. This article presents a mutation analysis of the GJB2, GJB6, OTOF and MTRNR1 genes in 252 patients with sensorineural non-syndromic hearing loss. Thirty-one different mutations were identified in GJB2 and GJB6 in 86 of the 252 (34%) patients. We describe for the first time two new mutations in GJB2: the missense mutation c.29 T>C (p.Leu10Pro) in the N terminal domain and c.326 G>T (p.Gly109Val) in the intracytoplasmic domain of connexin 26. This work shows the high prevalence of GJB2 mutations in the Argentinean population, with frequencies that are comparable to those of the Mediterranean area. Most important, it adds two novel GJB2 mutations to be taken into consideration in the genetic diagnosis of non-syndromic sensorineural hearing loss.